’CURVED-NORMAL’ VERTEBRAL MUTANTS IN CIRRHINA M RIG ALA - Chonder, S L (Indian Journal of Fisheries, 2011)
This paper reports for the first time the occurrence of curved and normal vertebral mutations in hypophysed Cirrhina mrigala fry